Workloads placed on adolescent cricket players: A pilot study. Issue 1 (February 2019) - Pote, Lee; Christie, Candice J
Cricket players nowadays are faced with increased physical demands, and as a result, it is important to manage their workload, particularly to control and predict risk of injury. While this has been investigated at an elite level, few studies have looked at the workloads placed on adolescent cricket players. The purpose of this study was therefore to determine the workloads placed on school boy cricketers, specifically within a South African context. Twelve male school boy cricketers between the ages of 16 and 19 years participated in the study. Match and practice data were collected over a period of 74 days and included number of shuttles run (batsmen), number of deliveries bowled (bowlers) as well as central ratings of perceived exertion (RPE). Injury data were also collected. These data were then used to determine the acute:chronic (a:c) workload ratio (two-week rolling average) as well as session RPE (sRPE). Fast bowlers delivered more balls during matches compared to practices, whereas batsmen ran more shuttles at practices compared to matches. Session RPE was higher for matches compared to practices. There did not appear to be a relationship between workload and injury risk; however, this may have been due to the small sample size. It was concluded that it is important to monitor individual workloads of players. Also, intensities of practices need to be increased to match game demands. Lastly, the study design was effective and the methods used were found to be appropriate for a larger population.